Versatile question answering systems: seeing in synthesis. (10th March 2011) - Mittal, Sparsh; Mittal, Ankush
Recent advances in massive information storage and growth of internet have led to increased necessity of tools such as search engines and QA systems to get meaningful answers from the vast amount of information. The complex questions appearing in real-life generally require multiple techniques or sub-division of question at various levels. Several practical systems have been developed to explore this. This paper reviews state-of-art QA systems which provide enhanced and versatile functionality at various levels in their architecture and then makes the following contributions: 1) it provides useful overview of research trends and recent developments in the area of QA; 2) the paper introduces and defines basic design parameters for any QA system; 3) it resolves semantic heterogeneity by clarifying the meaning and context in which different terms are used by different researchers; 4) it classifies the existing QA systems in broad groups, based on the point at which versatility (multiplicity) is introduced/handled in the system; 5) by developing a unified view of existing frontiers of QA systems, it provides clear directions for future research and development in the area.